EVALUATING ENGLISH INTENSIVE COURSE BOOK FOR STUDENTS OF ISLAMIC STATE UNIVERSITY OF JEMBER: USERS PERSPECTIVES - Sa’adah, Nailah‘ Ainayis; Munir, Ahmad; Indarti, Titik (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study evaluated how effectively the English Intensive Course book supports non‑English major students at the Islamic State University of Jember, focusing on its alignment with Cunningsworth’s eight evaluation criteria. An explanatory mixed‑methods design combined a Likert‑scale questionnaire (n = 20 students, 2 tutors) with semi‑structured interviews. Quantitative data were analyzed descriptively, while interview transcripts underwent thematic coding to triangulate and enrich survey findings. Overall mean scores ranged from 3.22 to 3.72 (4‑point scale), indicating strong agreement that the book meets program aims, offers well‑sequenced language content, and covers the four skills. Participants praised the grammar‑driven progression and integration of Islamic themes. Key weaknesses were the absence of answer keys, limited listening‑speaking tasks, and scarce multimedia support. Tutors also reported insufficient pedagogical guidance in the teacher’s manual. It provides actionable recommendations, embedding feedback mechanisms, metacognitive study‑skills training, and QR‑linked audio resources, that can inform future textbook design for intensive language programs in similar settings.